uvrC Gene Function in Excision Repair in Toluene-Treated Escherichia coli - Sharma, Surendra (1979)
We have examined the role of the uvrC gene in UV excision repair by studying incision, excision, repair synthesis, and DNA strand reformation in Escherichia coli mutants made permeable to nucleoside triphosphates by toluene treatment. After irradiation, incisions occur normally in uvrC cells in the presence of nicotinamide mononucleotide (NMN), a ligase-blocking agent, but cannot be detected otherwise. We conclude that repair incisions are followed by a ligation event in uvrC mutants, masking incision. However, a uvrC polA12 mutant accumulates incisions only slightly less efficiently than a polA12 strain without NMN. Excision of pyrimidine dimers is defective in uvrC mutants (polA(+) or polA12) irrespective of the presence or absence of NMN. DNA polymerase I-dependent, NMN-stimulated repair synthesis, which is demonstrable in wild-type cells, is absent in uvrC polA(+) cells, but the uvrC polA12 mutant exhibits a UV-specific, ATP-dependent repair synthesis like parental polA12 strains. A DNA polymerase I-mediated reformation of high-molecular-weight DNA takes place efficiently in uvrC polA(+) mutants after incision accumulation, and the uvrC polA12 mutant shows more reformation than the polA12 strain after incision. These results indicate that normal incision occurs in uvrC mutants, but there appears to be a defect in the excision of pyrimidine dimers, allowing resealing via ligation at the site of the incision. The lack of NMN-stimulated repair synthesis in uvrC polA(+) cells indicates that incision is not the only requirement for repair synthesis.